The Reconstruction Of Male Masculinity On Tiktok: A Gen Z Perspective - Daffa Faisal Afdala; Nurhanifah (Jurnal Ilmu Sosial dan Humaniora, 2026)
This study aims to examine the reconstruction of masculinity among men on TikTok and how audiences interpret the biased standards produced by the platform. Using a qualitative phenomenological approach, data were collected through in-depth interviews with Gen Z men and analyzed using NVivo to identify thematic patterns. The results show that masculinity on TikTok has shifted from traditional concepts toward a more performative, visual, and lifestyle-based identity. Masculinity is constructed through practices of curated identity, symbolic performance, and lifestyle display, all of which are influenced by algorithms and digital culture. On the other hand, these emerging standards create pressures such as comparison pressure and lifestyle pressure. However, audiences are not passive; they actively interpret content through dominant, negotiated, and oppositional readings. Thus, masculinity on TikTok becomes a dynamic arena of meaning contestation between media representation and individuals’ social experiences.